INFLUENCE OF PRODUCT QUALITY AND DISTRIBUTION ON ONLINE SHOPPING SATISFACTION - Haris Budi Kusuma; Raihana Daulay (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study is to: (1) determine and analyze the effect of product quality on consumer satisfaction shopping online e-commerce Lazada, (2) determine and analyze the effect of distribution on consumer satisfaction online shopping Lazada e-commerce, and (3) determine and analyze the effect of product quality and distribution on consumer satisfaction online shopping e-commerce Lazada. The approach used in this research is explanatory. The population in the study were all active students of the management study program as many as 2456 students and the research sample as many as 124 students. Data collection techniques in this study used interviews and questionnaires. The data analysis technique in this study uses the Classical Assumption Test, Multiple Linear Regression, t-test and F-test, and the Coefficient of Determination. While the data processing in this study used the SPSS 25 software program. Partially there was a significant effect of product quality on online shopping satisfaction at Lazada ecommerce for UMSU students. There is a significant distribution effect on online shopping satisfaction at Lazada e-commerce for UMSU students, and simultaneously product quality and distribution variables affect online shopping satisfaction in Lazada e-commerce for UMSU students.